Association of gestational weight gain rate with infant birth weight and cesarean delivery: A prospective cohort study in Nepal. - Jyoti Nepal; Kalpana Chaudhary; Bikram Adhikari; Abha Shrestha; Archana Shrestha; Sangita Pudasainee Kapri; Shristi Rawal (PLOS Global Public Health)
Gestational weight gain (GWG) is linked to pregnancy outcomes, such as birth weight and delivery mode, though research in low-income countries like Nepal is limited. We examined the association of GWG rate with infant birth weight and cesarean delivery in a prospective cohort of 191 pregnant women in Nepal, using data collected from August 2018 to August 2019 at a peri-urban hospital in Dhulikhel. Participants included women with singleton, full-term live births, with GWG rate calculated from weight gain between the second and late pregnancy stages, divided by the weeks in between. GWG rate categories-adequate, inadequate, or excessive-were defined by pre-pregnancy Body Mass Index (BMI) specific to GWG recommendations from the 2009 Institute of Medicine report. Ethical approval was obtained from Institutional Review Board of Kathmandu University and Rutgers University. Statistical analyses in SPSS and Stata revealed that 52.4% of mothers exceeded the recommended GWG rate, particularly among overweight and obese women (0.4 ± 0.2 kg/week and 0.5 ± 0.2 kg/week, respectively). The average birth weight was 2964.9 ± 407.0 grams, with 12% of infants classified as low-birth-weight. Cesarean delivery was recorded in 45% of the women. After controlling for factors like age, education, ethnicity, occupation, parity and BMI, each 1 kg/week increase in GWG from the second to third trimester correlated with a 392-gram increase in birth weight (β = 391.9, 95%CI = 67.2-716.7, p = 0.01), while excessive GWG rate led to a 148-gram increase over adequate GWG rate (β = 148.1, 95%CI = 8.7-287.5, p = 0.03). However, GWG rate was not significantly linked to cesarean delivery. These findings suggest that maternal GWG rate positively affects infant birth weight but not cesarean delivery, underscoring the need for larger studies to explore GWG rate's effects on maternal and neonatal outcomes.